A Phase I Study of Concurrent Weekly Carboplatin and Paclitaxel Combined With Intensity-Modulated Pelvic Radiotherapy as an Adjuvant Treatment for Early-Stage Cervical Cancer Patients With Positive Pelvic Lymph Nodes. Issue 7 (1st September 2013) - Mabuchi, Seiji; Takahashi, Ryoko; Isohashi, Fumiaki; Yokoi, Takeshi; Ito, Kimihiko; Tsutui, Tateki; Ogata, Toshiyuki; Yoshioka, Yasuo; Ogawa, Kazuhiko; Kimura, Tadashi
Abstract : Objectives: The objective of this study was to determine the maximum tolerated dose (MTD) and acute dose-limiting toxicities (DLTs) of intravenous carboplatin plus paclitaxel combined with intensity-modulated pelvic radiotherapy (pelvic IMRT) as an adjuvant treatment for early-stage cervical cancer patients with positive pelvic lymph nodes. Methods: Women with uterine cervical cancer who were treated with radical hysterectomy and pelvic lymphadenectomy and displayed positive pelvic lymph nodes were eligible for this study. The patients were postoperatively treated with pelvic IMRT (50.4 Gy). The concurrent weekly chemotherapy consisted of carboplatin (area under the curve [AUC], 2) and paclitaxel (starting at 35 mg/m 2 and escalating by 5 mg/m 2 in 3 patient cohorts). The primary end point of the escalation study was acute DLT that occurred within 30 days of the completion of radiation therapy. Results: Nine patients were enrolled and treated at 2 dose levels until DLT occurred. The median age of the patients was 47 years (range, 28–66 years). The median radiotherapy treatment time was 39.5 days (range, 38–64 days). At dose level I (35 mg/m 2 paclitaxel), 2 grade 3 leukopenia and a neutropenia were observed, but no DLT occurred. At dose level II (40 mg/m 2 paclitaxel), the first patient experienced a grade 2 hypersensitive reaction, which resulted in discontinuation of planned treatment. Thus, 2 more patients were evaluated at this dose level. Of these, 1 patient experienced febrile neutropenia, which was considered to be a DLT, and the other patient experienced long-lasting grade 3 leukopenia and grade 3 neutropenia, which resulted in the discontinuation of chemotherapy for 2 weeks (a DLT). We then evaluated 3 more patients at dose level 1, but no DLT occurred. The MTD of paclitaxel and carboplatin was thus defined as 35 mg/m 2 and an AUC of 2.0, respectively. Conclusions: Weekly paclitaxel/carboplatin and pelvic IMRT is a reasonable adjuvant treatment regimen for cervical cancer patients after radical hysterectomy. The MTD of paclitaxel and carboplatin for future phase II trials of this regimen is 35 mg/m 2 and an AUC of 2.0, respectively.